2003
DOI: 10.1088/0305-4470/36/19/310
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing of a coupled state of two spinors

Abstract: Abstract. The notion of spin squeezing involves reduction in the uncertainty of a component of the spin vector S below a certain limit. This aspect has been studied earlier [1,2] for pure and mixed states of definite spin. In this paper, this study has been extended to coupled spin states which do not possess sharp spin value. A general squeezing criterion has been obtained by requiring that a direct product state for two spinors is not squeezed. The squeezing aspect of entangled states is studied in relation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The investigation of squeezed states of light [1] is of fundamental interest, and has applications to practical precision measurements [2,3]. Recently, spin squeezed states for an ensemble of atoms [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24] have become important, with potential applications to atomic interferometers and precise atomic clocks. For quantum information applications [25], the close relation between atomic spin squeezing and quantum entanglement [26,27,28,29,30] enhance the importance of atomic spin squeezing.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of squeezed states of light [1] is of fundamental interest, and has applications to practical precision measurements [2,3]. Recently, spin squeezed states for an ensemble of atoms [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24] have become important, with potential applications to atomic interferometers and precise atomic clocks. For quantum information applications [25], the close relation between atomic spin squeezing and quantum entanglement [26,27,28,29,30] enhance the importance of atomic spin squeezing.…”
Section: Introductionmentioning
confidence: 99%
“…It may be pointed out here that squeezed radiation states have already received considerable attention as basic ingredients of nonclassicality in the theory of continuous variable QIS [6]. On the other hand, in discrete variable QIS, which is based mainly on two-level systems (atoms with two internal levels or qubits), there have been intense efforts recently [7,8,9,10,11,12,13,14] to understand the intrinsic link between spin squeezing and entanglement. In this paper, we report theoretical efforts on developing quantitative measures of spin squeezing and also relate spin squeezing with quantum entanglement in multiatomic (multiqubit) systems.…”
Section: Introductionmentioning
confidence: 99%
“…While complete characterization of multi-particle entanglement still remains a major task, collective behaviour such as spin squeezing [1, 2, 3,4,5,6,7,8,9,16,17,18,19,20,21,22,23,24,25,26,27], exhibited by multi-atom systems, has been proposed as a signature of quantum correlation between the atoms. A connection between spin squeezing and the nature of quantum entanglement has been explored [26,27] and it is shown that the presence of spin squeezing essentially reflects pairwise entanglement.…”
Section: Introductionmentioning
confidence: 99%